Fabrication of magnetic and recyclable In2S3/ZnFe2O4 nanocomposites for visible light photocatalytic activity enhancement. (20th January 2020) - Zhao, Wenye; Huang, Yun; Su, Chunyan; Gao, Yepen; Tian, Wenhui; Yang, Xudong
Abstract: In this work, magnetic In2 S3 /ZnFe2 O4 nanocomposites were fabricated via a two-step solvothermal process, which In2 S3 loading amount on ZnFe2 O4 support medium could be controlled by changing reaction mass. Investigation revealed that the photocatalytic activity of In2 S3 /ZnFe2 O4 nanocomposites was uperior to pure In2 S3 and ZnFe2 O4 for the degradation of MB driven by visible light. The improved photocatalytic activity may be stemming from the synergy effect of In2 S3 and ZnFe2 O4, resulting in the enhanced visible light absorbance and higher separation efficiency of the photo-generated charge carriers. Significantly, this sort of nanocomposites could rapidly be separated through an external magnetic field, and five successive cycle experiments have proved that it was stable and recyclable. Finally, a possible mechanism related to the separation of charge and photocatalytic decomposition of MB was also provided.